Cataract Blindness and Simulation-Based Training for Cataract Surgeons : An Assessment of the HelpMeSee Approach - James R. Broyles, Peter Glick (RAND Corporation, 2013)
Cataract accounts for about half of all cases of blindness worldwide, with an estimated 20 million people suffering from bilateral cataracts (World Health Organization website, undated). The overwhelming majority of these cases are in developing countries, where blindness and visual impairment (VI) can have enormous negative impacts on the quality of life, along with reducing life expectancy and economic productivity. Yet the great majority of cases of cataract VI can be cured by quick and inexpensive surgical procedures, with very high success rates in developing country contexts. Manual Small Incision Cataract Surgery (MSICS) is a safe, lowcost, and very rapid surgical method for cataract removal that has been shown to have success rates equivalent to more complex and costly methods.